Do consumers follow their heart or mind when purchasing global brands? Empirical insights. Issue 1 (1st January 2023) - Naseem, Nayyer; Yaprak, Attila
Abstract: This study explores the extent of direct and mediated influence of consumer affinity and perceived value on consumers' purchase intentions, in the realm of global brands. Using attitude theory and the elaboration likelihood model as conceptual anchors, a theory-driven model is tested in a between-subject design. Findings reveal that consumer affinity has a substantial and direct influence, while perceived value has a substantial mediated influence, with dominating affective component of the attitude. Perceived value has a stronger influence than consumer affinity on purchase intentions, but consumer aspirations make affinities stronger. These findings advance the consumer behavior literature and enhance managerial decision-making in market segmentation, targeting, and positioning contexts.